Managing Teacher Competence Improvement through Leadership, Professional Development, and Digital Innovation: A Systematic Literature Review - Ahmad Masruri; Juliana Wahid; Norman, Efrita; Hasbian, Yanti; Komarudin (Journal of Educational Management Research, 2025)
Teacher competence is a key factor in improving education quality and student outcomes in the 21st century. This systematic literature review analyzes 41 peer-reviewed studies published between 2020 and 2025, examining the roles of leadership, professional development, and digital innovation. Using PRISMA methodology and a critical assessment framework, the review identifies that instructional and transformational leadership enhance teacher competence by promoting collaboration, innovation, and accountability. Effective professional development models include mentorship, coaching, and learning communities, particularly when adapted to local contexts. Digital innovations—such as AI, gamification, and mobile learning—offer new pathways for teacher growth but face challenges related to infrastructure, training, and socio-economic disparities. The review highlights significant inequalities between developed and developing regions, especially in rural areas. Findings underscore the need for equity-focused policies, localized implementation of global frameworks, and sustainable investment in teacher development. Enhancing teacher competence remains a global and local priority to prepare students for the demands of an increasingly complex world.